2013
DOI: 10.1371/journal.pone.0074570
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Electronic Data Collection System for Large-Scale Surveys of Neglected Tropical Diseases

Abstract: BackgroundLarge cross-sectional household surveys are common for measuring indicators of neglected tropical disease control programs. As an alternative to standard paper-based data collection, we utilized novel paperless technology to collect data electronically from over 12,000 households in Ethiopia.MethodologyWe conducted a needs assessment to design an Android-based electronic data collection and management system. We then evaluated the system by reporting results of a pilot trial and from comparisons of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
128
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(140 citation statements)
references
References 30 publications
5
128
5
Order By: Relevance
“…Our quantitative results on data quality are consistent with findings from other evaluations [3,6,7,10,11,1519]. On paper forms, the level of missing data increased with the complexity of skip patterns, while almost the opposite pattern was seen in EDC, showing the usefulness of programmed automatic skip patterns in guiding interviewers to the correct questions.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Our quantitative results on data quality are consistent with findings from other evaluations [3,6,7,10,11,1519]. On paper forms, the level of missing data increased with the complexity of skip patterns, while almost the opposite pattern was seen in EDC, showing the usefulness of programmed automatic skip patterns in guiding interviewers to the correct questions.…”
Section: Discussionsupporting
confidence: 89%
“…In other evaluations, respondents tended to have accepted the new methods [8,23], but some concerns were raised over ‘outsider’ technology [4,14], and one study found a higher refusal rate with EDC [15]; the respondents we spoke to had no reservations regarding the technology. This acceptance in our setting may be due to the long-running nature of the project and good relationships with the community.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As in previous studies, our findings support the use of electronic tools to address some of the known challenges of data management in traditional paper-based health surveys. They include a reduction in turnaround time for results availability, improvements on quality of data, and cost savings [28,29]. We found that electronic surveys, compared with the paper method, involved fewer staff, shortened survey procedures, and improved quality of data at lower costs.…”
Section: Discussionmentioning
confidence: 99%